The Concept of Text in Paul Ricoeur and its Relationship with the Contemporary Brief Lyrics (2010)
This essay is a reflection about the notion of text in Paul Ricoeur and its possible applications to the contemporary brief proem. The main purpose of the essay is to present the hermeneutical problem and its relation with the theory of the text in the wo